👤

f)3(2x-3)=-39
g) 2(x-8) + 4 = -6
h)5(x-1)<0
i)2(x+5)+3<-9
j)3+2(x+2)<5
k)1+4(x-1)<-7
l)5(2+3x)<-5



Răspuns :

F)6X-9=-39rezulta 6x=-39+9rezulta 6x = -30 rezulta x = -30 : 6 = -5
g)2x-16+4=-6 
2x-12=-6
2x=-6+12
2x=6
x= 6:2 =3
h)5x-5<0
5x<5
x<5:5 
x<1 
aici trebuie sa specifici cui apartine x ;
daca apartine lui Z lui N
f)6x-9 = -39

6x=-39+9
6x= -30
x =-5

g)2x-16+4=-6
2x-12=-6
2x=-6+12
2x=6
x=3

h)5x-5<0
5x <5 |:5
x <1  ⇒x∈(-α;1)

i)2x+10+3 <-9
2x +13 < -9
2x < -9-13
2x < -22 |:2
x < -11  ⇒x ∈(-α;-11)

j)3+2x+4 <5
2x +7 <5
2x < 5-7
2x < -2 |:2
x < -1 ⇒x∈(-α;-1)

k)1+4x-4 < -7
4x-3 < -7
4x < -7+3
4x < -4 |:4
x < -1⇒ x∈(-α;-1)

l)10+15x < -5
15x < -5-10
15x < -15 |:15
x < -1 ⇒x ∈(-α;-1)